James Cone's Legacy for White Christians. Issue 3 (2nd April 2020) - Norris, Kristopher
ABSTRACT: This article explores James Cone's lesson and legacy for white Christians. Specifically, it analyzes Cone's claim that whites can "become black." Cone insists that a process of conversion to blackness "means that white people are prepared to deny themselves (whiteness), take up the cross (blackness), and follow Christ (black ghetto)." In this essay, I will draw upon Cone's writings and original interview material to construct an outline of these three steps of becoming black. Making sense of what it means to convert to blackness begins with first analyzing his specific challenge to white theology, then his concepts of blackness and the Black Christ, and finally, the praxis of these three steps – that is, what does it look like, practically, to follow the black Christ as a white person.